Long‐term outcomes of Group D retinoblastoma eyes during the intravitreal melphalan era. Issue 12 (24th June 2017) - Berry, Jesse L.; Shah, Sona; Bechtold, Mercy; Zolfaghari, Emily; Jubran, Rima; Kim, Jonathan W.
Abstract: Background: To evaluate outcomes of Group D retinoblastoma (Rb) eyes during the intravitreal melphalan era. Procedure: Retrospective chart review of patients diagnosed with Group D Rb from 2011 to 2016 was done. Overall, 76 Group D eyes of 68 patients were included; salvage therapy included systemic chemoreduction with vincristine, etoposide, and carboplatin with local consolidation, followed by intravitreal injection of melphalan for recurrent or persistent seeding. External beam radiation was not used as a treatment modality. Primary outcome measurement was globe salvage. Results: Of 76 Group D eyes, 24 were enucleated primarily and 52 were treated with intent to salvage the globe. Systemic chemoreduction salvaged 25 of 52 eyes (48%). Tumor recurrences were diagnosed in 27 eyes (52%); five with massive retinal recurrences underwent enucleation and 22 were treated with intravitreal melphalan injection. Of the 22 injected eyes, 14 (64%) were salvaged and eight required enucleation primarily for retinal recurrences. Success in eradicating vitreous seeds was 100%. The Kaplan–Meier 3‐year survival estimate for treated eyes is 76.5% (95% CI: 61.4–86.3). Median follow‐up for the group of 76 Group D eyes was 29.5 months (SD 17.9 months). Conclusion: During a 6‐year period that included the initiation of intravitreal melphalan at our institution, the salvage rate of treated Group D eyes was 75% (39/52 eyes). Intravitreal melphalan was utilized for ocular salvage in 42% (22/52 eyes). Systemic chemoreduction combined with intravitreal melphalan for seeding demonstrated a high overall salvage rate for Group D eyes in this cohort.